Prospects and Challenges of Cataloguing in the Digital Age - Ajani, Florence Olabisi; Sulyman, Abdulakeem Sodeeq (Communicate: Journal of Library and Information Science, 2023)
The digital age offers technological support to cataloguers to simplify the processes of cataloguing of information resources. This paper investigates the prospects and challenges of cataloguing in the digital age. It uses the topology design to structure its major headings into stages, based on their importance and relevance to the phenomenon being discussed. Thus, after justifying the rationale for understudying the prospects and challenges of cataloguing in the digital age, this paper explores the nexus between digital age and cataloguing before explaining the major prospects of cataloguing in the digital age and finally discussed the challenges of cataloguing in the digital age. It concludes that digital age has unbundled the restrictions of availability of bibliographic records of information resources beyond the four-walls of libraries, which has driven cooperations and collaborations among libraries. Its main recommendation is that adequate IT infrastructure required for digital cataloguing should be made available in libraries.